Desain Lembar Kerja Berbasis Argumentasi untuk Meningkatkan Kemampuan Argumentasi Ilmiah pada Materi Pemanasan Global (Universitas Negeri Surabaya, 2023)
This study aims to analyze the results of the validity of argumentation-based worksheets to improve students' scientific argumentation skills on global warming material. The method used in this study is the R&D method with 4D development. There are three stages used in this research, namely, defining and gathering various information related to the product; design, designing a content framework or outline; and development, namely, the implementation of product planning. Validity was assessed with a Likert scale. The aspects evaluated are the content presented, language, graphics, and construction. The analysis technique was carried out by calculating the results of the validity of the worksheets from 3 validators, namely two expert lecturers in the field of physics and a high school physics teacher. The research results obtained are from the content aspect validity of 100% in the very valid category; from the language aspect, the validity is 93.8% in the very valid category; from the graphical aspect, the validity is 95.8% in the very valid type, and construct validity is 97 .2% in the very valid category. Based on these results, the average worksheet validity value is 96.7%, with a very valid category. So it can be concluded that argumentation-based worksheets to improve scientific argumentation skills on global warming material are suitable for use as research instruments and can also be used in the learning process, especially in class X. So argumentation-based worksheets can facilitate students in practicing scientific argumentation skills in school, especially on global warming material.